Transcriptomic analysis of nickel exposure in Sphingobium sp. ba1 cells using RNA-seq - M. Volpicella; C. Leoni; C. Manzari; M. Chiara; E. Picardi; E. Piancone; F. Italiano; A. D’Erchia; M. Trotta; D. S. Horner; G. Pesole; L. R. Ceci (Scientific Reports, 2017)
Abstract Nickel acts as cofactor for a number of enzymes of many bacteria species. Its homeostasis is ensured by proteins working as ion efflux or accumulation systems. These mechanisms are also generally adopted to counteract life-threatening high extra-cellular Ni2+ concentrations. Little is known regarding nickel tolerance in the genus Sphingobium. We studied the response of the novel Sphingobium sp. ba1 strain, able to adapt to high Ni2+ concentrations. Differential gene expression in cells cultured in 10 mM Ni2+, investigated by RNA-seq analysis, identified 118 differentially expressed genes. Among the 90 up-regulated genes, a cluster including genes coding for nickel and other metal ion efflux systems (similar to either cnrCBA, nccCBA or cznABC) and for a NreB-like permease was found. Comparative analyses among thirty genomes of Sphingobium species show that this cluster is conserved only in two cases, while in the other genomes it is partially present or even absent. The differential expression of genes encoding proteins which could also work as Ni2+-accumulators (HupE/UreJ-like protein, NreA and components of TonB-associated transport and copper-homeostasis systems) was also detected. The identification of Sphingobium sp. ba1 strain adaptive mechanisms to nickel ions, can foster its possible use for biodegradation of poly-aromatic compounds in metal-rich environments.